An assessment of drought severity on the vegetation health in the Jaguari-Jacarei watershed - Campos Carvalho, Fernando Luiz de [UNESP]; Alcantara, Enner [UNESP]; IEEE (Ieee, 2018)
Droughts are natural events that can cause water scarcity and can consequently have undesired political, social and environmental impacts. Since the end of 2013 the southeastern Brazil has suffered the worst drought in 55 years. This severe drought imposes water shortages for approximately 40 million people. Land use and land cover changes may drastically influence local climate, which increases the surface temperature. The aim of this work was to assess the negative impact of aforementioned drought on the vegetation health in a representative watershed in southeastern Brazil. The preliminary results showed the potential of satellite data in identify the drought periods and to classify the severity.
Keywords: Natural hazards; Cantareira System; vegetation health index; land surface temperature